HUBUNGAN BIOMARKER INFLAMASI C-REAKTIF PROTEIN DENGAN LAJU ENDAP DARAH PADA PASIEN TERKONFIRMASI COVID-19 - Renowati Renowati; Waslaini Waslaini; Fitra Wahyuni (Ensiklopedia of Journal, 2022)
Abstract: China country. It spreads very quickly, namely through physical contact through the nose, mouth, and eyes, and develops in the lungs (C-Reactive Protein). CRP is an acute phase protein synthesized in the liver for non-specific monitoring of local and systemic disease. The erythrocyte sedimentation rate is the rate at which erythrocytes settle in a vertical tube. Research has been carried out to determine the title of the relationship between C-Reactive Protein Levels and Blood Sedimentation Rates in Covid-19 Confirmed Patients. Samples in this study were 60 samples. Then it was found that there were 45 men with a percentage (58.3 %) and a female sex with a percentage of 25 people (41.7 %), and the average c-reactive protein level 477.63 mg/dl and the sedimentation rate was 3.258,33 mm /hour. Then the results of statistical tests obtained results of 0.001 < 0.05. the conclusion is that there is a relationship between levels of c-reactive protein and levels of erythrocyte sedimentation rate in patients suspected of covid-19 with sufficient correlation criteria.Keywords: Corona virus, CRP levels, LED